2006
DOI: 10.1302/0301-620x.88b4.16498
|View full text |Cite
|
Sign up to set email alerts
|

The culture of articular chondrocytes in hydrogel constructs within a bioreactor enhances cell proliferation and matrix synthesis

Abstract: Bovine and human articular chondrocytes were seeded in 2% alginate constructs and cultured for up to 19 days in a rotating-wall-vessel (RWV) and under static conditions. Culture within the RWV enhanced DNA levels for bovine chondrocyte-seeded constructs when compared with static conditions but did not produce enhancement for human cells. There was a significant enhancement of glycosaminoglycans and hydroxyproline synthesis for both bovine and human chondrocytes. In all cases, histological analysis revealed enh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 22 publications
1
16
0
Order By: Relevance
“…These applied dynamic culturing conditions (perfusion/fluid flow, hydrostatic pressure or dynamic compressive loading) enhance developing neo-tissues F o r P e e r R e v i e w 4 through enhanced nutrient delivery and metabolic waste removal (15)(16)(17) and/or by providing a mechanical stimulus to the cells (6,(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29). For example, Akmal et.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These applied dynamic culturing conditions (perfusion/fluid flow, hydrostatic pressure or dynamic compressive loading) enhance developing neo-tissues F o r P e e r R e v i e w 4 through enhanced nutrient delivery and metabolic waste removal (15)(16)(17) and/or by providing a mechanical stimulus to the cells (6,(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29). For example, Akmal et.…”
Section: Introductionmentioning
confidence: 99%
“…al. (17), showed that bovine encapsulated alginate hydrogels cultured in a rotating-wall vessel (RWV) enhanced DNA, glycosaminoglycan and collagen levels. However, histological analysis revealed enhanced Safranin-O staining in the peripheral regions of the constructs compared with the central region.…”
Section: Introductionmentioning
confidence: 99%
“…The alginate cell culture system was chosen since only a three-dimensional construct is able to maintain the phenotype of the chondrocytes: maintenance of the production of cartilage specific matrix proteins such as collagen type II and aggrecan and a low proliferation rate [26][27][28]. The diameter of the alginate beads measures 2-3 mm imposing the question whether sufficient oxygen is delivered to the cells for phototoxic reactions to occur [29].…”
Section: Discussionmentioning
confidence: 99%
“…To date, no consensus has been reached concerning optimal cell densities in cell-based therapeutic methods. In different reports cell numbers ranged from 2.5 × 10 5 [53] to 1 × 10 7 per cm 2 [54]. Another study reported that MSCs require an even higher cell density during the chondrogenesis process [55].…”
Section: Culture Conditionsmentioning
confidence: 99%